Pengaruh gaya hidup harga dan kualitas produk terhadap keputusan pembelian produk sepatu Adidas di kota palu: Gaya hidup harga dan kualitas produk terhadap keputusan pembelianpeoduk sepatu adidas - Lisda; Bachri, Syamsul; Syarifuddin, Umar; Mandala Putra, Setiawan (JURNAL MANAJEMEN MOTIVASI, 2026)
This study aims to analyze the influence of lifestyle, price, and product quality on purchasing decisions for Adidas shoes in Palu City. The method used was quantitative, with a survey approach involving 135 respondents through purposive sampling and a Likert-scale questionnaire. The analysis used multiple linear regression. The results show that lifestyle and price significantly influence purchasing decisions, while product quality does not. Simultaneously, all three variables have a significant effect. This study has implications for companies in designing lifestyle-based marketing strategies and pricing.